TROPICAL FORESTRY LEGAL FRAMEWORKS AND IMPLEMENTATION CHALLENGES IN SOUTHEAST ASIA - Chantal Ngoa; Elvis Ewane; Lucie Etong (Yayasan Adra Karima Hubbi, 2026)
Tropical forests in Southeast Asia play a critical role in biodiversity conservation, carbon sequestration, and supporting local livelihoods. Rapid deforestation, illegal logging, and land-use conflicts continue to undermine forest sustainability, highlighting persistent gaps between legal frameworks and practical implementation. Understanding these challenges is essential for developing effective governance strategies that balance ecological, social, and economic objectives. The study aims to evaluate the existing legal frameworks governing tropical forestry in Southeast Asia and to identify key barriers to effective implementation. It examines how laws, policies, and regulations are operationalized across multiple countries, with particular attention to enforcement mechanisms, stakeholder engagement, and alignment with sustainable forest management goals. A mixed-methods approach was employed, combining legal document analysis, interviews with policymakers, forestry experts, and community representatives, and comparative assessment across selected Southeast Asian countries. Data were analyzed to assess the coherence, effectiveness, and practical challenges of forest governance systems. Findings reveal that while comprehensive legal frameworks exist, enforcement gaps, inconsistent policy application, limited technological monitoring, and insufficient community participation impede effective implementation. Countries with integrated governance mechanisms and participatory approaches demonstrate improved compliance and forest conservation outcomes. The study concludes that aligning legal frameworks with technological support and active stakeholder engagement is critical to enhancing tropical forest governance. Recommendations include adaptive policies, strengthened monitoring systems, and participatory mechanisms to ensure sustainable forest management.